Development of Mobile Learning Media on Newton's Laws Using the Appy Pie Application - Renny Firdawati; Maison Maison; Nazarudin Nazarudin (Postgraduate, University of Mataram, 2021)
This research and development aim to develop mobile learning media using the Appy Pie application for high school students. The research and development stages are carried out using the ADDIE model. The instruments used for validation in this development research are (1) a validation questionnaire filled in by the validator to determine the media's feasibility, (2) a teacher and student response questionnaire to assess user perceptions of the media used. There are two kinds of data collecting and analysis methods: qualitative methods to collect data and describe comments and suggestions for improvement from the validators and quantitative methods to collect and analyze responses from teachers and students. Based on the validation results of media development carried out by design, material, and media experts, it is stated that the media is valid and can be tested. The results of the teacher's response obtained a percentage of 90% in the very good category, the results of student responses in the one-on-one trial obtained a rate of 91.56% in the very good category, the results of student responses in small group trials received a percentage of 90.27% in the very good category